Mike and Tony : best friends - Ziefert, Harriet; Siracusa, Catherine (New York, N.Y., U.S.A. : Viking Kestrel, 1987)
Best buddies Mike and Tony enjoy doing everything together, from playing baseball to riding bikes, so their argument over a pillow fight keeps them apart for only a short while.
Elementary School Library Collection (Bro-Dart)
1.5
K-3
Keywords: Friendship -- Fiction; Friendship -- Fiction